ANALISIS YURIDIS TENTANG PERLINDUNGAN KONSUMEN DALAM PENGGUNAAN OBAT PELANGSING TANPA IZIN BADAN PENGAWAS OBAT DAN MAKANAN (BPOM)(Studi Kasus Beauslim) - Aulia Zahrah (2023)
The Food and Drug Supervisory Agency (BPOM) is an official institution or agency appointed by the government to carry out the function of monitoring drugs and food and cosmetics in Indonesia. All products in Indonesia need to be registered with BPOM so that their quality is maintained and safe before being widely distributed in the community. However, along with the times many products sold in Indonesia do not have a distribution permit, one of which is a slimming drug from Beauslim. Although currently Beauslim no longer sells its products, Beauslim has falsified the Register Numbers of other products to be circulated. Seeing this problem, the author examines the legal sanctions for using Register Numbers belonging to other products and circulating them in the market and the form of legal protection for consumers who are victims of the actions of business actors. This research is normative juridical research sourced from case studies and literature studies. The results of this research can be an education for victims and the public to be careful in buying slimming products especially if they have side effects that can interfere with the health of the body and harm the community if food safety is not through appropriate procedures. To reduce the circulation of illegal drugs in Indonesia, the Food and Drug Monitoring Agency (BPOM) together with related institutions must maximize a stricter monitoring system, so that consumer safety and health can be protected.